2006
DOI: 10.1111/j.1365-2125.2006.02730.x
|View full text |Cite
|
Sign up to set email alerts
|

Continuous vs. intermittent cefotaxime administration in patients with chronic obstructive pulmonary disease and respiratory tract infections: pharmacokinetics/pharmacodynamics, bacterial susceptibility and clinical efficacy

Abstract: AimTo compare the pharmacokinetics/pharmacodynamics, antibiotic resistance and clinical efficacy of continuous (CA) vs. intermittent administration (IA) of cefotaxime in patients with obstructive pulmonary disease and respiratory infections. MethodsA randomized controlled prospective nonblinded study was per formed in 93 consecutive hospitalized patients requiring antibiotics for acute exacerbations of chronic obstructive pulmonary disease. Forty-seven patients received 2 g of cefotaxime intravenously over 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 24 publications
1
54
0
1
Order By: Relevance
“…Van Zanten et al, reported similar clinical success rates in patients with acute exacerbations of COPD receiving either CI or thrice-daily administration of cefotaxime [257]. [374].…”
Section: Mortalitymentioning
confidence: 86%
See 4 more Smart Citations
“…Van Zanten et al, reported similar clinical success rates in patients with acute exacerbations of COPD receiving either CI or thrice-daily administration of cefotaxime [257]. [374].…”
Section: Mortalitymentioning
confidence: 86%
“…Numerous clinical comparative studies have been conducted with beta-lactams testing various dosing strategies in various patient populations including critically ill patients [85,86,151,166,169,171,172,[241][242][243][246][247][248][249][250][251][252], patients receiving extracorporeal renal circuit [244,245,253], trauma patients [254], patients with malignant diseases [255], patients with intra-abdominal infections [256], patients with chronic obstructive pulmonary disease (COPD) [257,258] and nonspecific hospitalized patients [173,[259][260][261][262] (Table 1-2). These studies have not shown whether alternative dosing approaches (i.e., CI and EI) are advantageous nor which patient groups may benefit.…”
Section: Clinical Outcomesmentioning
confidence: 99%
See 3 more Smart Citations